A Brief Historical Summary of the Constitutional and Judicial Assessment of the Problems of Federalism in Russia - S. L. Sergevnin (Теоретическая и прикладная юриспруденция)
The article is devoted to the consideration of the positions of the Constitutional Court of the Russian Federation on issues of state structure, in particular the principles of the federal structure, the status and powers of the constituent entities of the Russian Federation, the delimitation of subjects of jurisdiction, and the organization of public authority. The author considers the main differences between a federal and confederal structure, type and other features of a federal structure, enshrined in the 1993 Constitution of the Russian Federation.